Mechanism of cargo sorting into small extracellular vesicles. Issue 1 (1st January 2021) - Chen, Yiwen; Zhao, Yuxue; Yin, Yiqian; Jia, Xiaonan; Mao, Lingxiang
ABSTRACT: Extracellular vesicles (EVs) are special membranous structures released by almost every cell type that carry and protect some biomolecules from being degraded. They transport important signaling molecules involved in cell communication, migration, and numerous physiological processes. EVs can be categorized into two main types according to their size: i) small extracellular vesicles (sEVs), such as exosomes (30–150 nm), released from the fusion of multivesicular bodies (MVBs) with the plasma membrane, and ii) large EVs, such as microvesicles (100–1000 nm). These are no longer considered a waste product of cells, but regulators of intercellular communication, as they can transport specific repertoires of cargos, such as proteins, lipids, and nucleic acids to receptor cells to achieve cell-to-cell communication. This indicates the existence of different mechanisms, which controls the cargos sorting into EVs. This review mainly gives a description about the biological roles of the cargo and the sorting mechanisms of sEVs, especially exosomes.